Tummu and par(as)-ṣeḫru. Note on Two Measures of Weight at Nuzi - Zaccagnini, Carlo
HSS 15 228f.; tummu ‘1/4 shekel’ (syn. rebūtu); BAR.TUR not mišlu ṣiḫru but pár-ṣeḫru, var. pa-ra-ṣé-eḫ-rù ‘1/3 shekel’.